2014
DOI: 10.1038/srep07248
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II acting on brain AT1 receptors induces adrenaline secretion and pressor responses in the rat

Abstract: Angiotensin II (AngII) plays important roles in the regulation of cardiovascular function. Both peripheral and central actions of AngII are involved in this regulation, but mechanisms of the latter actions as a neurotransmitter/neuromodulator within the brain are still unclear. Here we show that (1) intracerebroventricularly (i.c.v.) administered AngII in urethane-anesthetized male rats elevates plasma adrenaline derived from the adrenal medulla but not noradrenaline with valsartan- (AT1 receptor blocker) sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Brain Ang II acts to induce several physiological responses, including stimulation of water and sodium intake, vasopressin secretion and BP increase by activating AT 1 receptors (Averill and Diz, ; Chen and Pan, ). We also previously demonstrated that centrally administered Ang II increases the release of adrenaline from the adrenal medulla in the rat, suggesting activation of the sympatho‐adrenomedullary system (Nakamura et al ., ). Moreover, our previous findngs showed that centrally administered Ang II at a dose that does not affect BP or the peripheral adrenaline levels shortens the intercontraction interval (ICI) by acting on the brain AT 1 receptors in rats (Kawamoto et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Brain Ang II acts to induce several physiological responses, including stimulation of water and sodium intake, vasopressin secretion and BP increase by activating AT 1 receptors (Averill and Diz, ; Chen and Pan, ). We also previously demonstrated that centrally administered Ang II increases the release of adrenaline from the adrenal medulla in the rat, suggesting activation of the sympatho‐adrenomedullary system (Nakamura et al ., ). Moreover, our previous findngs showed that centrally administered Ang II at a dose that does not affect BP or the peripheral adrenaline levels shortens the intercontraction interval (ICI) by acting on the brain AT 1 receptors in rats (Kawamoto et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In some experiments, acute bilateral adrenalectomy (ADX) [plus hydrocortisone (5 mg/kg per animal, i.m.)] was performed just before the cannulation by an abdominal midline incision (Shimizu et al, 2006;Nakamura et al, 2014). Subsequently, each rat was placed in a stereotaxic apparatus for the brain (SR-6R; Narishige, Tokyo, Japan) until the end of each experiment, as described previously by our laboratory (Shimizu et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The study showed chronic pretreatment with telmisartan (3‐30 mg/kg) suppressed central Ang II‐induced effects (drinking response, arterial pressure increase and release of vasopressin) . Change in BP by AT1 receptor antagonist administration might affect micturition reflex via sympathetic nerve activity . Current data showed that peripherally administered telmisartan (3 or 10 mg/kg) at doses which do not affect BP, suppressed the central Ang II‐induced ICI reduction in rats.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, the previous report showed that centrally administered Ang II stimulated the release of adrenaline from the adrenal medulla in rats. This data suggests central Ang II activates the sympatho‐adrenomedullary system, a characteristic feature of the stress response. Moreover, different types of stress stimulate the Ang II release and also increase the expression of brain AT1 receptors .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation